Perturbation of phosphatidylethanolamine synthesis affects mitochondrial morphology and cell-cycle progression in procyclic-form Trypanosoma brucei. - Signorell, A; Gluenz, E; Rettig, J; Schneider, A; Shaw, M; Gull, K; Bütikofer, P (2009)
Phosphatidylethanolamine (PE) and phosphatidylcholine (PC) are the two major constituents of eukaryotic cell membranes. In the protist Trypanosoma brucei, PE and PC are synthesized exclusively via the Kennedy pathway. To determine which organelles or processes are most sensitive to a disruption of normal phospholipid levels, the cellular consequences of a decrease in the levels of PE or PC, respectively, were studied following RNAi knock-down of four enzymes of the Kennedy pathway. RNAi against ethanolamine-phosphate cytidylyltransferase (ET) disrupted mitochondrial morphology and ultrastructure. Electron microscopy revealed alterations of inner mitochondrial membrane morphology, defined by a loss of disk-like cristae. Despite the structural changes in the mitochondrion, the cells maintained oxidative phosphorylation. Our results indicate that the inner membrane morphology of T. brucei procyclic forms is highly sensitive to a decrease of PE levels, as a change in the ultrastructure of the mitochondrion is the earliest phenotype observed after RNAi knock-down of ET. Interference with phospholipid synthesis also impaired normal cell-cycle progression. ET RNAi led to an accumulation of multinucleate cells. In contrast, RNAi against choline-/ethanolamine phosphotransferase, which affected PC as well as PE levels, caused a cell division phenotype characterized by non-division of the nucleus and production of zoids.